Efficacy of preoperative dexamethasone for postoperative nausea and vomiting after laparoscopic cholecystectomy: a large‐scale, multicenter, randomized, double‐blind, placebo‐controlled trial in Japan. (19th October 2015) - Wakasugi, Masaki; Tori, Masayuki; Shimizu, Junzo; Kim, Yong Kook; Noda, Takehiro; Dono, Keizo; Takeda, Yutaka; Yamamoto, Tameyoshi; Oshima, Satoshi; Morimoto, Yoshikazu; Asaoka, Tadafumi; Eguchi, Hidetoshi; et al.
Abstract: Background: To assess the efficacy of preoperative dexamethasone for postoperative nausea and vomiting (PONV) after laparoscopic cholecystectomy (LC) in Japan. Methods: A total of 270 patients at eight hospitals were randomized to receive dexamethasone 8 mg ( n  = 136) or placebo ( n  = 134) intravenously before LC. The primary endpoint was the degree of PONV and antiemetic requirements within 24 h after LC. Secondary endpoints were postoperative complications, postoperative hospital stay, and cost of hospital stay. This study was registered: UMIN‐CTR (UMIN000003841). Results: Within 6 h after LC, 17% (23/136) of patients in the dexamethasone group versus 24% (32/134) in the placebo group reported nausea ( P  = 0.3), and 5% (7/136) versus 7% (10/134) reported vomiting ( P  = 0.2). Metoclopramide 10 mg was used 0.09 ± 0.31 versus 0.14 ± 0.35 times ( P  = 0.2). From 6 to 24 h, 10% (14/136) versus 13% (17/134) reported nausea ( P  = 0.5), and 5% (7/136) versus 5% (7/134) reported vomiting ( P  = 0.8). Metoclopramide was used 0.04 ± 0.19 versus 0.03 ± 0.17 times ( P  = 0.8). Postoperative complications and postoperative hospital stay did not differ significantly between the two groups, but the cost of hospital stay was slightly higher in the dexamethasone group ( P  < 0.05). Conclusions: Routine use of preoperative dexamethasone for PONV after elective LC in Japan was not shown to have a clinical advantage. Abstract : Highlight Wakasugi and colleagues set out to evaluate the prophylactic efficacy of preoperative dexamethasone for postoperative nausea and vomiting after elective laparoscopic cholecystectomy. Preoperative dexamethasone showed no clinical advantage, as it failed to significantly reduce the incidence of postoperative nausea and vomiting, while it increased the cost of hospital stay.